Peningkatan Kemampuan Komunikasi Matematis Siswa SMA Negeri 1 Panggarangan Melalui Metode Tutor Sebaya Dengan Media Youtube - Saepudin, Sandi; Pratidiana, Deni; Rifa'i, Rusdian (Universitas Mathla'ul Anwar Banten, 2024)
This research was motivated by the lack of variety in teaching carried out, as well as the low mathematical communication skills of students at SMAN 1 Panggarangan for the 2024/2025 academic year. This research aims to find out whether there is an increase in the mathematical communication skills of students who receive peer tutoring using YouTube media and students who receive conventional learning using Power Point media on composition of functions and inverse functions. The method used in this research is quasi-experimental. The population in this study were students of SMAN 1 Panggarangan. The samples in this research were students from XI-E as the experimental class and class XI-F as the control class. The instrument used in this research was a test of mathematical communication skills with 5 questions, in the form of a presentation, where previously the questions had been tested for validity, reliability, difficulty index and distinguishing power and were tested first and the questions were declared suitable for use. The data analysis used was a test of the difference between two means which had previously been tested for normality and homogeneity. After researchers conducted research using a learning model based on data exposure, researcher findings, and the discussion that has been described, it can be concluded that there has been an increase in students' mathematical communication skills obtained by peer tutoring and conventional learning. In other words, the increase in mathematical communication skills of students who receive peer tutoring using YouTube media is higher than students who receive conventional learning using Power Point media.